(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Fifteen species of fungi belonging to ten genera were found to be associated with Leea macrophylla Roxb. ex Harnem. The species are Alternaria tenuissima (Kunze ex Pers.) Wiltshire, Aspergillus flavus Link, Aspergillus fumigatus, Aspergillus niger van Tiegh, Chaetomium Kunze, Colletotrichum musae (Berk. & Curt.) Arx, Colletotrichum dematium (Pres. Ex Fr.) Grove, Curvularia pallescens Boedijn, Fusarium moniliforme Shelden, Fusarium sp., Melasmia Lev, Penicillium sp., Rhizopus sp., Trichoderma harzianum Pers. and Trichoderma viride Pers. This is the first record of association of the fungi with Leea macrophylla from Bangladesh. All the identified fungi were tested for their pathogenic potentiality. Colletotrichum dematium, Curvularia pallescens, and Fusarium sp. produced symptoms on artificially inoculated leaves of Leea macrophylla. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12972 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 257-262, 2012